2018
DOI: 10.1029/2017jc013686
|View full text |Cite
|
Sign up to set email alerts
|

Recently Accelerated Oxygen Consumption Rates Amplify Deoxygenation in the Baltic Sea

Abstract: Many coastal seas suffer from expanding bottom‐water deoxygenation and hypoxia primarily because of excessive nutrient loads from land. The Baltic Sea in northern Europe has one of the largest anthropogenically induced oxygen‐deficient bottom zones in the world. Despite the decrease of nutrient supply after the 1980s, recently observed oxygen consumption rates are higher than ever observed, limiting the impact of natural ventilation by oxygen‐enriched saltwater intrusions. We have estimated oxygen consumption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
49
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 48 publications
5
49
0
Order By: Relevance
“…In December 2014, a strong saline water inflow from the North Sea was observed, which was the third strongest ever recorded (Mohrholz et al, 2015). Although the salinity in December 2014 was comparable to other years, a remarkable increase in salinity was observed in the following several months.…”
Section: Flux Densitymentioning
confidence: 82%
“…In December 2014, a strong saline water inflow from the North Sea was observed, which was the third strongest ever recorded (Mohrholz et al, 2015). Although the salinity in December 2014 was comparable to other years, a remarkable increase in salinity was observed in the following several months.…”
Section: Flux Densitymentioning
confidence: 82%
“…The Baltic Sea is a brackish sea and has very limited water exchange with marine water originating from the North Sea and therefore has long flushing times in the order of 2-3 decades (e.g. Meier 2007;Meier et al 2018b). The average depth is about 50 m. It is permanently stratified in most areas due to a strong halocline at 60-80 m depths (e.g.…”
Section: Brief Description Of the Study Areamentioning
confidence: 99%
“…Together with the Danish straits this area constitutes the pathway for the more or less sporadic severe inflows of salt-rich water masses from the North Sea to the Baltic Sea (Major Baltic inflows, MBIs) which can be monitored far into the deep Baltic Proper and which play an important role in controlling oxygen conditions in the deep Baltic (e.g. Matthäus and Franck 1992;Meier et al 2018b).…”
Section: Brief Description Of the Study Areamentioning
confidence: 99%
“…A significant nutrient decline has been observed at the BE Time-Series Station since the mid-1980s, however, Lennartz et al (2014) found that bottom O 2 concentrations were still decreasing over the past 60 years. The ongoing oxygen decline was attributed to the temperature-enhanced O 2 consumption in the bottom water (Meier et al, 2018) and a prolongation of the stratification period at the BE Time-Series Station (Lennartz et al, 2014). Please note that the trends in nutrients and O 2 concentrations were detected based on the data collection which lasted for approximately 30 and 60 years, respectively, while the N 2 O observations at BE Time-Series…”
Section: Trend Analysismentioning
confidence: 95%